Street Food Consumption and Hygiene Issues in George Town, Penang - Othman, Anis Solehin Hussain at; Dawood, Sharifah Rohayah Sheikh (European Publisher, 2019)
The era of globalization has witnessed the growing phenomenon of consumption or consumerism in parallel with socio-cultural change and improvement in economic progress. However, Penang street food poor business placement causes issue of cleanliness and food safety to emerge. This study was carried out to explore the aspects of street food consumption in the city of George Town and its relation to hygiene issues. The George Town city area was selected because it is known as a World Heritage Site by UNESCO and a gastronomic city that turn it into a popular tourist destination in Malaysia. This study focuses on hawkers’ attitude towards street food cleanliness. It also reflects the consumers’ perception on food and hygiene issues. Questionnaire instruments have been used in this study through random sampling methods. The population of the study involved 200 respondents, consisting of 100 local consumers/local tourists and 100 international tourists whom experienced consuming street foods around the city of George Town. For the hawker’s category, the researchers have collected 30 respondents to answer the questionnaires. Researchers have also used in-depth interviews with seven street food vendors/hawkers. The findings revealed that hygiene issues amongst street food operations are serious issue although there were variations in terms of findings for local and international consumers. Thus, the government and street food vendor/hawkers should address the issues of hygiene practices through various initiatives and measures.